GOLDMAN SACHS REPORT CAN BE LETHAL FOR SOUTH AFRICA DUE TO UNEMPLOYMENT AND OTHER SALIENT ISSUES: UNPACKING THE REALITIES OF FISCAL BALANCES AND TRADE DEFICIT (Singaporean Journal of Business Economics and Management, 2013)
This paper attempts to look at and discuss the government of South Africa's viewpoint or rather spin on fiscal balances in terms of budget forecast. On the other hand the Goldman Sachs report can end up being lethal to South Africa. It argues that the trade deficit of R19 billion is dangerously wide and that salaries are up, but spending is strained. There is evidence that after nearly 20 years of democracy that white South Africans have grown wealthier on an aggregate basis, whilst the number of South Africans living below the poverty line has been reduced by nine percent. The paper depicts and shows the advances made under democratic government, post 1994 and outlines the challenges that remain. The paper will also project on dogma and denial by the trade unions from transforming South African society and the economy. It argues that it is the crucial role of trade unions should and could play in the technological, social and political circumstances of the 21st risk the development of democracy and further marginalize the poor and stymie the emergence of the developmental state that it aspires to attain.